Antidrug policies and the need to confront the colombian vulnerabilities (2009)
None of the prevalent paradigms helps explain why the great majority of countries that can cultivate coca and corn poppy and produce cocaine and heroin do not make it, that is, why the illegal production of those drugs is so concentrated being so profitable; or why in the countries where traditional cultivations of coca were common, big dealing organizations did not occur. It is not either explained why illegal drug abuse has tended to be concentrated in few countries, or why in some countries stimulants are primarily abused while in others narcotics are mainly consumed; why antidrug policies show unsatisfactory results and which would be the effects of applying other policies; why, in spite of the fact that Bolivia and Peru previously had extensive and rooted cultivations of coca, the powerful traffickers did not appear there but in Colombia. This article proposes a new paradigm. In order to advance in that direction, the literature of criminology on the reasons for somebody to commit crimes is researched. Then some basic questions are sought to be answered: Which factors contribute to criminality? Are there enough causes or factors for the development of illegal industries or only some necessary factors and other simply contributive ones? Once the answers to these questions are obtained it would be possible to proceed to evaluate the effectiveness of antidrug policies. Some conclusions are summarized at the end.